Follistatin-like I promotes endometriosis by increasing proinflammatory factors and promoting angiogenesis. Issue 1 (30th December 2021) - Lei, Sha-Ting; Li, Ming-Qing; Cao, Yan-Ling; Hou, Shu-Hui; Peng, Hai-Yan; Zhao, Dong; Sun, Jing
Abstract : Endometriosis (EMS) is a chronic benign inflammatory disease characterized by the growth of endometrial-like tissue in aberrant locations outside of the uterine cavity. Angiogenesis and abnormal immune responses are the fundamental requirements of endometriotic lesion survival in the peritoneal cavity. Follistatin-like I (FSTL1) is a secreted glycoprotein that exhibits varied expression levels in cardiovascular disease, cancer and arthritis. However, the role of FSTL1 in the development of EMS remains to be fully elucidated. Results of the present study demonstrated that the expression of FSTL1 was significantly increased in ectopic endometrial stromal cells (ESCs) and peritoneal fluid from patients with EMS, compared to the control group. Both conditions of hypoxia and estrogen treatment induced human ESCs to produce increased levels of FSTL1 and disco-interacting protein 2 homolog A (DIP2A). Furthermore, the expression levels of DIP2A, IL8 and IL1β were increased in FSTL1 overexpressed HESCs. Additionally, FSTL1 treatment increased the proliferation of HUVECs in a dose-dependent manner in vitro and markedly increased the tube formation of HUVECs. Moreover, treatment with FSTL1 facilitated M1 polarization of macrophages, increased the secretion of proinflammatory factors and inhibited the expression of scavenger receptor CD36. Results of the present study suggested that the elevated expression of FSTL1 may play a key role in accelerating the development of EMS via enhancing the secretion of proinflammatory factors and promoting angiogenesis.